Acquired epidermodysplasia verruciformis: clinical presentation and treatment update. (17th August 2021) - Moore, Stephen; Rady, Peter; Tyring, Stephen
Abstract: Acquired epidermodysplasia verruciformis (AEV) is a form of epidermodysplasia verruciformis (EV) that is most commonly found in immunocompromised or immunosuppressed patients. EV is commonly associated with human papillomavirus (HPV), which is often found in EV and AEV lesions. Clinical presentation of AEV in patients with organ transplantation, HIV+, congenital HIV+, hematological diseases, and other iatrogenic immunosuppression are reviewed. Treatment options include topical cidofovir, topical retinoids, topical imiquimod, topical glycolic acid, HPV 9‐valent vaccine, acitretin, improving cellular immunity, and changing transplant medication to mycophenolate mofetil.